Integrating Effects of Human Physiology, Psychology, and Individual Variations on Satiety–An Exploratory Study - Ni, Dongdong; Smyth, Heather E.; Cozzolino, Daniel; Gidley, Michael J. (Frontiers in Nutrition, 2022)
Satiety can influence food intake, and as a consequence has the potential to affect weight and obesity. Human factors such as physiology and psychology are likely to be important in determining satiety. However, it is not well understood how these factors (individual variations) alone or combined contribute to satiety feelings. In this study, three plant-based foods were used as mid-morning snack for 52 participants to evaluate satiety response. The foods were served ad libitum until participants felt comfortably full prior to satiety monitoring. The study explored diverse human factors (n=30) that might contribute to satiety including those related to oral physiology, metabolic factors, body composition and psychology. It identified important variables for satiety as well as the interactions among them and the influences of age, gender, and low satiety phenotype (consistently lower reported fullness scores) on satiety. Overall, combinations of factors rather than individual ones contributed to self-reported satiety. Food factors (e.g. type, composition) had limited effects, but there were only three types used in the study. The combination of metabolic factors [respiratory quotient, age, and body energy usage type (e.g. carbohydrate or fat)], oral sensitivity & processing, personality traits (agreeableness, conscientiousness, and neuroticism), and eating behavior were the most important for explaining individual satiety responses. Older participants had significantly higher reported satiety than younger participants, associated with significant differences in oral physiology, increased body fat, and mature psychological characters. Moreover, different satiety phenotypes had significant differences in relationships with body fat, oral physiology, personalities, food neophobia, and eating behaviors. The results of this study indicate that much greater insights into the factors determining satiety responses can be obtained by combining multiple food and human physiological and psychological characteristics. This study used more diverse measures of individual variation than previous studies of satiety and points the way towards a more holistic approach to understanding the (control of) perceptions of fullness at both individual and group levels.